Drug-Induced Lung Disease (Organizing Pneumonia) Associated with Mesalazine - E. V. Smirnova; D. A. Strelkova; S. A. Ratchina; S. N. Avdeev; O. V. Aryutina; O. Yu. Karpova (Туберкулез и болезни лёгких)
The article describes a clinical case of mesalazine-related lung disease in a patient treated for ulcerative colitis.